Polyvinylidene Fluoride (PVDF)/Modified Clay Hybrid Membrane for Humic Acid and Methylene Blue Filtration - Edi Pramono; Gadis Prihatin Wahyu Sejati; Sayekti Wahyuningsih; Candra Purnawan (Indonesian Journal of Chemistry, 2023)
This research studied the impact of silanized clay modification on performance and antifouling Poly(vinylidene fluoride) (PVDF) membrane toward humic acid and methylene blue filtration. Clay modification was carried out by using 3-aminopropyltriethoxysilane (APS) to produce modified clay (Clay-APS). Hybrid membranes were prepared by phase inversion for humic acid and methylene blue filtration. Hybrid membranes were characterized by measuring surface hydrophilicity, water flux, rejection, and antifouling properties. Clay and Clay-APS modification increased hybrid membrane surface hydrophilicity, as indicated by increasing the β fraction and decreasing the water contact angle. The PVDF/Clay and PVDF/Clay-APS hybrid membranes showed high permeability and selectivity with the highest water flux values of 24.2 L m−2 h−1. The rejections for humic acid and methylene blue were 98.8 and 99.3%, respectively. The highest antifouling property was obtained from the PVDF/Clay-APS hybrid membrane, with a flux recovery ratio was 96.0%. The PVDF/Clay hybrid membrane performance and antifouling properties showed that the membranes have the potential for water treatment.